2022
DOI: 10.1111/and.14403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leukocytospermia on the outcomes of assisted reproductive technology

Abstract: Leukocytospermia is one of the common causes of male infertility, and its effects on the clinical outcomes of assisted reproduction are controversial. There are no recommendations for the management of leukocytospermia in cases of assisted reproductive technology (ART). To investigate the impact of leukocytospermia on ART, we retrospectively compared the clinical outcomes in ART couples with or without leukocytospermia and further analysed the impact of the insemination method itself by split insemination trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(52 reference statements)
0
4
1
Order By: Relevance
“…Our findings are consistent with several prior studies which have similarly demonstrated no adverse impact of leukocytospermia on clinical outcomes and fertilization rates [ 2 , 9 ]. While some studies have shown reduced semen analysis parameters and negative clinical outcomes in the presence of leukocytospermia [ 3 – 8 , 11 ], our results did not demonstrate this. The potential impact of various sperm processing techniques, sample sizes, and patient etiologies may account for the differing results seen in prior studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with several prior studies which have similarly demonstrated no adverse impact of leukocytospermia on clinical outcomes and fertilization rates [ 2 , 9 ]. While some studies have shown reduced semen analysis parameters and negative clinical outcomes in the presence of leukocytospermia [ 3 – 8 , 11 ], our results did not demonstrate this. The potential impact of various sperm processing techniques, sample sizes, and patient etiologies may account for the differing results seen in prior studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies, however, have suggested no adverse impact on fertilization rate, quality of embryos, and clinical outcomes including implantation rate when comparing IVF cycles in the presence of leukocytospermia to those cycles without leukocytospermia [ 2 , 9 , 10 ]. One study demonstrated that despite lower semen analysis parameters in the leukocytospermia group at the time of IVF and ICSI, there was no significant difference in the clinical pregnancy rate and live birth rate compared to the non-leukocytospermia group [ 11 ]. A recent meta-analysis of 28 case-control studies comparing the fertilization rate after ART for 254 leukocytospermic cases and 3613 non-leukocytospermic controls also found no significant difference between the two groups [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 13 ] showed that there were no correlations between the leukocyte concentration, basic semen parameters, sperm cell number, and damaged DNA and 8-OHdG expression in a group of infertile men. Furthermore, some researchers did not indicate that leukocytes significantly influence assisted reproductive technology outcomes [ 66 , 67 ]. Both in original research [ 66 ] and meta-analysis [ 67 ], the harmful effect of leukocytospermia on in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some researchers did not indicate that leukocytes significantly influence assisted reproductive technology outcomes [ 66 , 67 ]. Both in original research [ 66 ] and meta-analysis [ 67 ], the harmful effect of leukocytospermia on in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) was not confirmed. Groups of patients, irrespective of leukocytospermia, did not differ in assessed embryo parameters, the course of pregnancy, or live birth rates.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Yilmaz et al found a negative impact of leukocytospermia on fertilization and embryo development rates after ICSI [183]. Yet, other reports demonstrated that the presence of more than 10 6 leukocytes/mL in the ejaculate that were used for insemination has no effect on the outcome of assisted reproduction by IVF and ICSI [252][253][254][255]. In a metaanalysis including 254 leukocytospermic and 3613 non-leukocytospermic patients in six and five studies, respectively, Castellini et al did not observe an effect of the presence of an excessive number of leukocytes on the fertilization rate after IVF or ICSI outcomes (six studies) [256].…”
Section: Relevance Of Leukocytospermiamentioning
confidence: 99%